Pongamia: A possible option for degraded land restoration and bioenergy production in Indonesia - Leksono, B.; Rahman, S.A.; Larjavaara, M.; Purbaya, D.A.; Arpiwi, N.L.; Samsudin, Y.B.; Artati, Y.; Windyarini, E.; Sudrajat, D.J.; Aminah, A.; Maulana, A.M.; Bhatta, K.P.; et al. (Center for International Forestry Research, 2022)
Indonesia has 14 million ha of degraded and marginal land, which provides very few benefits for human well-being or biodiversity. This degraded land may require restoration. The leguminous tree Pongamia pinnata syn. Milettia pinnata (pongamia) has potential for producing biofuel while simultaneously restoring degraded land. However, there is limited information on this potential for consideration. This paper aims to address the scientific knowledge gap on pongamia by exploring its potential as a biofuel and for restoring degraded land in Indonesia. We applied a literature review to collect relevant information on pongamia, which we analysed through narrative qualitative and narrative comparative methods with careful compilation and scientific interpretation of retrieved information. The review revealed that pongamia occurs naturally across Indonesia; in Sumatra, Java, Bali, Nusa Tenggara and Maluku. It can grow to a height of 15–20 m and thrives in a range of harsh environmental conditions. Its seeds can generate up to 40% crude pongamia oil by weight. It is a nitrogenfixing tree that can help restore degraded land and improve soil properties. Pongamia also provides wood, fodder, medicine, fertilizer and biogas. As a multipurpose species, pongamia holds great potential for combating Indonesia’s energy demand and restoring much of the country’s degraded land. However, the potential competition for land and for raw materials with other biomass uses must be carefully managed.